HEALTH STATUS OF CORAL REEF ECOSYSTEM AT LIVINGSEAS BALI CONSERVATION SITE, PADANGBAI, BY SEEING THE AVAILABILITY OF BUTTERFLYFISH (CHAETODONTIDAE) AS A BIOINDICATOR - Rafael Iskandar, Benedict
Coral reefs are an ecosystem that has a high diversity which is important in providing ecosystem services, of which, being a habitat for different kinds of marine organisms as well as coastal human communities. Coral reef structures are made from the result of coral animal calcification, which are becoming prone to environmental disturbances, causing live coral coverage to decrease annually. Thus, a lot of effort has been done to restore the coral reef ecosystem, one of which is done at Padangbai, Bali by Livingseas Bali, a dive center with a focus on tourism that has started the artificial live coral reef (reefstar) conservation effort since 2019. Of course, in running a coral reef conservation effort, an assessment on the health status of said coral reef needs to be done. Chaetodontidae fishes are one of the reef fish whose life quite depends on live coral reef health, so the availability of these fishes could be a bioindicator to assess the health status of a coral reef ecosystem. This research aims to assess the health status of the restored hard corals conservation using the butterflyfish (Family Chaetodontidae) as an indicator species. This research is done at the Livingseas Bali, Padangbai conservation site. Data were taken on three transects, each having the length of 25 m with different depths and different age groups of the artificial reef. The method used to collect fish data is the belt transect, while coral coverage data were collected using the PIT (Point Intercept Transect) method. Measured water quality data were temperature, pH, salinity, and electro conductivity. From the data analysis, it is shown that the percentage of coral reefs at every transect are 67,33% (Transect 1), 60,67% (Transect 2), 37,67% (Transect 3) with a total 55,22%, which according to the criteria of the Percentage of The Coral Reef Coverage by the Environmental Ministry Decision No.4 Year 2001, is included into the good category. The calculated mortality index of the whole site is very small (0,0036). Chaetodontidae fish communities at the Livingseas site consists of 10 species. The abundance of Chaetodontidae fish population at every transect is; 78 for Transect 1, 43 for Transect 2, and 29 for Transect 3 with the biggest population of species recorded coming from the Chaetodon kleinii species. Further analysis has shown that coral coverage has a statistically significant positive correlation with the abundance of Chaetodontidae fishes. This shows that Chaetodontidae fishes are good bioindicators for the health of coral reefs, as shown from the good coverage of live coral reef with the quite good existence of Chaetodontidae fishes as well.